2019
DOI: 10.1016/j.jsxm.2019.03.273
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Recovery Profiles After Cessation of Androgen Deprivation Therapy for Prostate Cancer

Abstract: Introduction Androgen deprivation therapy (ADT) is frequently used in the treatment of prostate cancer worldwide. Variable testosterone (T) recovery profiles after ADT cessation have been cited. Aim To evaluate T recovery after cessation of ADT. Methods We reviewed our institutional prospectively maintained database of patients with prostate cancer who receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…In another single-institutional retrospective study by Nascimento et al, coexisting diabetes and older age were associated with delayed normalization of testosterone. 10 In contrast, Murthy et al found no correlation between age and time to testosterone recovery to >6 nmol/L. In this small study of 56 patients who were treated with neoadjuvant ADT followed by prostate radiation therapy (64-74 Gy), the majority had normalized testosterone by 1 year after the last ADT injection.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…In another single-institutional retrospective study by Nascimento et al, coexisting diabetes and older age were associated with delayed normalization of testosterone. 10 In contrast, Murthy et al found no correlation between age and time to testosterone recovery to >6 nmol/L. In this small study of 56 patients who were treated with neoadjuvant ADT followed by prostate radiation therapy (64-74 Gy), the majority had normalized testosterone by 1 year after the last ADT injection.…”
Section: Discussionmentioning
confidence: 69%
“…Time to full testosterone Some of the findings of our study, such as an association between increasing age, lower baseline testosterone level, or diabetes and longer testosterone recovery, concur with previous studies. 8,[10][11][12]26 Based on a multivariable Cox regression, Spiegel et al found a significant association between testosterone recovery and pretreatment testosterone level, ADT duration, and body mass index, respectively. 11 In this study, the 2-year cumulative incidence of testosterone recovery was 65.7% in patients treated with short-term ADT (median duration: 6 months; range, 3.0-18.4 months) and 53.1% in those treated with long-term ADT (median duration: 24.3 months; range, 3.0-41.9 months).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For NHT, a luteinizing hormone releasing hormone (LHRH) agonist/antagonist and/or antiandrogen drug are usually selected. Several previous studies demonstrated that testosterone recovery to the normal level after hormonal therapy took several months [16][17][18][19][20][21][22][23]. On the other hand, the duration that NHT affects the pattern of BCR after RP has not been examined.…”
Section: Introductionmentioning
confidence: 99%